Compliance with “Five Moments For Hand Hygiene” in Reducing the Incidence of Healthcare Associates Infections (HAIs): A Systematic Review - Ernawati, Yayuk; Muhith, Abdul; Zahroh, Chilyatiz (Chakra Brahmanda Lentera Institute, 2024)
Background: Hand hygiene is essential in breaking the transmission chain of infections. Scientifically, it has been proven to prevent and reduce the spread of harmful microorganisms, thereby decreasing the incidence of Healthcare-Associated Infections (HAIs). The purpose of this study is to find out if compliance with hand hygiene within five moments can reduce the number of healthcare associates' infections. Methods: This research method uses a literature review using the PRISMA technique. Data was obtained from journals, including PubMed, Clinical Key, Science Direct, and Google Scholar, from 2020-2024, based on the results of the identification based on inclusion criteria. A feasibility review was obtained, and twenty articles were received for review Results: Compliance with hand hygiene within five seconds can reduce the number of HAIs specifically. Conclusion: Compliance with the Five Moments for hand hygiene is a simple and effective way to reduce the rate of Healthcare-Associated Infections (HAIS) in hospitals